Moult in the Stripe-throated Bulbul, Pycnonotus finlaysoni: sexual differences and timing - Somboon Kamtaeja" (Science Faculty of Chiang Mai University, 2019)
Moult of wing feathers in passerine birds occurs annually to maintain flight abilities. This process is costly due to the high energy requirements involved in the synthesis of new feathers. This study presents basic information about the moulting of primaries and secondaries in the adult Stripe-throated Bulbul (Pycnonotus finlaysoni), a sexually monomorphic passerine, living in the seasonal tropical forests of northern Thailand. Specifically, we examined the moult differences between males and females. The moult season began in early June and lasted until mid November (2009). The primary moult began approximately 20 days before the secondary moult. Our comparative analysis of the moult process between the sexes showed that males started to moult earlier than females for both primary and secondary feathers. The moult process took longer for the males than for the females with an approximate primary moult of 136 days for males (n = 11) and 118 days for females (n = 16), and a secondary moult of 114 days and 101 days for males (n= 11) and females (n = 16), respectively. This is probably because of a sexual bias in breeding time investment. Males are involved earlier in the breeding process e.g. singing and establishing territory. Females have more responsibility later in the cycle e.g. incubating eggs and nestling care.